Stability Analysis of a Mathematical Model on the Revitalization Efforts of Local Languages in East Kalimantan - Sudirman Sudirman; Masduki Zakaria (West Science Interdisciplinary Studies, 2026)
Local languages are an essential part of cultural identity, but are increasingly endangered due to modernization and globalization. This study aims to develop a mathematical model based on a dynamic system to describe the revitalization of local languages in East Kalimantan. The model divides the population into four compartments: individuals who cannot speak the local language , participants in local language education , language promoters , and technology users in local language learning . The model assumes a closed population with key parameters, including the education transmission rate , transition to promotion , and the technology utilization rate . The analysis involves determining the equilibrium points, calculating the basic reproduction number  using the Next Generation Matrix method, and assessing the local stability of the system. The results show that indicates the potential sustainability of local languages, while  suggests a tendency toward extinction. Simulations reveal that increasing language promotion and technology utilization can significantly raise  making their combination an effective strategy to maintain the vitality of local languages.